Nifedipine-Induced Changes in the Electrohysterogram of Preterm Contractions: Feasibility in Clinical Practice - Maartje P. G. C. Vinken; C. Rabotti; M. Mischi; J. O. E. H. van Laar; S. G. Oei (Obstetrics and Gynecology International)
Objective. Evaluating changes in the power spectral density (PSD) peak frequency of the electrohysterogram (EHG) caused by nifedipine in women with preterm contractions. Methods. Calculation of the PSD peak frequency in EHG contraction bursts at different times of nifedipine treatment in women in gestational age 24 to 32 weeks with contractions. Results. A significant (P<.05) decrease of PSD peak frequency between EHG signals measured before and 15 minutes after administration of nifedipine. A significant (P<.05) decrease in PSD peak frequency comparing signals recorded within 24 hours after administration of nifedipine to signals 1 day after tocolytic treatment. A higher average PSD peak frequency for patients delivering within 1 week than that for patients delivering after 1 week from nifedipine treatment (P>.05). Conclusions. EHG signal analysis has great potential for quantitative monitoring of uterine contractions. Treatment with nifedipine leads to a shift to lower PSD peak frequency in the EHG signal.